Outcomes of Kidney Transplants From Toxoplasma-Positive Donors: An Organ Procurement and Transplant Network Database Analysis - Butani, Lavjay; Tancredi, Daniel (Transplant international, 2024)
There is a need to reconsider the acceptance of organs from donors considered suboptimal, in the absence of data. Toxoplasma antibody-positive donors (TPD) constitute one such group. The objective of our study was to compare graft survival in deceased donor renal transplant (Tx) recipients, stratified by Toxoplasma IgG status, using the Organ Procurement and Transplantation Network (OPTN) database. A log-linear event history regression model for graft failure categorized by Toxoplasma IgG status, adjusting for confounders was applied to first kidney-only Tx recipients from 2018 to 2022. Of the 51,422 Tx, 4,317 (8.4%) were from TPD. Acute rejection and graft failure (5% each) were similar between groups. Crude graft failure was 7.3 failures per 100 person-years for TPD recipients compared to 6.5 failures per 100 person-years for the Toxoplasma-negative group ( p 0.008). The crude failure rate ratio was 1.14 with an adjusted hazard rate ratio of 1.04 (95% CI: 0.94, 1.15, p 0.39). In renal Tx recipients, TPD graft recipients have comparable survival to Tx from Toxoplasma-negative recipients. While caution and close monitoring of recipients post-Tx for surveillance of disseminated toxoplasmosis are still warranted, our study suggests that patients can be successfully managed using TPD organs.